FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - Eddy Joni; Anita Fauziah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical about the effect of independent variables towards dependent variables. The independent variables of research are independent commisioner, audit committee, leverage, return on assets, company size, and sales growth. The dependent variables of research are tax avoidance.Data who used in this study is data manufacturing company listed on the Indonesia Stock Exchange (IDX) from period 2018-2020. There are 63 samples of manufacturing companies in this research with a total of 189 data that match the criteria. Criteria select using the purposive sampling method.This research is used multiple regression to test hypothesist. The result of this research are sales growth has influence on tax avoidance, and the variable independent commisioner, audit committee, leverage, return on assets, company size has no influence on tax avoidance